Managing Sustainable Mangrove Forests in Peninsular Malaysia - Jusoff, Kamaruzaman; Taha, Dahlan (2008)
Mangrove forests in Peninsular Malaysia are found mainly on the sheltered coasts, estuaries, rivers and some near-shore islands. Mangrove forests support a diverse range of animals and plants and are important breeding ground for a vast array of organisms. The importance of mangrove forests in providing invaluable goods and services both in economics and environmental terms are well understood and documented. Forestry Department Peninsular Malaysia (FDPM) has been keeping abreast with current issues at the national, regional and international levels in managing the mangrove forests. FDPM has always been fully committed to the implementation of the sustainable forest management practices and in line with current concerns such as climate change, conservation of biological diversity and natural calamities including tsunami, have brought about a heightened expectation to the forestry profession. The policy and management of mangrove forests have great impacts on the political, social, economic, ecological and environmental well- being of the country, and thus managing mangrove forests is very challenging to the department. Mangrove forests management system has undergone changes from merely managing for its wood produce, to a management system that incorporates multiple roles, protection and conservation. Systematic management of mangrove forests started as early as 1904, with the adoption of the first working plan for Mangrove Forests in Matang. The Matang mangroves are identified as the best described mangrove forests in the world and is an exemplary of the sustainable managed mangrove forests. The Matang mangroves is in its third ten-year period of the second rotation, and after more than 100 years of management, the forest is still intact, providing sustainable various goods and services. This in itself is a manifestation of the success of forest management practices that aptly earned Matang mangroves as the best managed mangrove forests in the world. Special emphasis to the protection of the mangrove forests is enshrined in the National Forest Policy 1978 (revised1992) and duly recognized and given specific attention in the National Forestry Act 1984 (revised 1993). Future management of mangrove forests in Peninsular Malaysia will adopt an integrated approach by further refining the current management approach and incorporating latest findings and updated information through more vigorous R&D, scientific expeditions and studies on mangrove forests. A paradigm shift to conserve biodiversity even in the management of production mangrove forests will be emphasized. The National Forestry Policy and other policies related to mangrove forests need to be revised from time to time to match prevailing conditions and requirements, to ensure the realization of its multi-functions in perpetuity. The success in the sustainable management of mangrove forests by FDPM has in fact contributed to the sustainability of the Wetlands in Malaysia which is crucial to the survival and future health of the earth too.